Food Variety and Nutritional Status Among Adolescents in MAN Bangkalan - Wibowo, Arlen Chandra Saputra; Arief, Ria Qadariah; Widayanti, Linda Prasetyaning (International Conference on Sustainable Health Promotion, 2025)
Food variety was one of the methods to improve nutritional status. Maintaining nutritional status is important to improve their productivity. This study aimed to determine the impact of food variety on the nutritional status of MAN Bangkalan students. The population of this research was students from MAN Bangkalan. This study used a cross-sectional design with a binary logistic regression analysis test, using simple random sampling with a total of 55 participants, consisting of 24 males and 31 females. The result was statistically significant p-value 0.009 < 0.05 with an OR of 1,645. The students who had a better variety of foods were more likely to have better nutritional status 1,6 times higher than students who did not do the same. Students needed to improve their food variety to maintain their nutritional status. Student could improve food variety by consuming foods from different sources. They could also increase food variety by choosing a more diverse range of snacks